Odpowiedź :
2³•4:2²=2³•2²:2²=2⁵:2²=2³
27:x•3⁵=3⁶ to 3³:x•3⁵=3⁶ to 3³:3²•3⁵=3¹•3⁵=3⁶ czyli x=3²
4⁴:x•16•64=4⁸ ==> 4⁴:x•4²•4³=4⁸ ==>
4⁴:x•4⁵=4⁸ ==> 4⁴:4¹•4⁵=4⁸ bo 4³•4⁵=4⁸ czyli x=4¹
625:5²:x:5²=1 ==> 5⁴:5²:x:5²=1 ==> 5²:x:5²
==> x=5⁰
Odpowiedź:
Szczegółowe wyjaśnienie:
27:x•3⁵=3⁶ to 3³:x•3⁵=3⁶ to 3³:3²•3⁵=3¹•3⁵=3⁶ czyli x=3²
4⁴:x•16•64=4⁸ ==> 4⁴:x•4²•4³=4⁸ ==>
4⁴:x•4⁵=4⁸ ==> 4⁴:4¹•4⁵=4⁸ bo 4³•4⁵=4⁸ czyli x=4¹
625:5²:x:5²=1 ==> 5⁴:5²:x:5²=1 ==> 5²:x:5²
==> x=5⁰
Odpowiedź:
Szczegółowe wyjaśnienie:
Odpowiedź:
Szczegółowe wyjaśnienie:
1)odp 2 do potęgi 3
2) odp 3 do potęgi 2
3) odp 4 do potegi 1
4) odp 5 do potęgi 0